UNRAVELING THE COMPLEX GENETIC ARCHITECTURE OF AUTISM SPECTRUM DISORDER: INSIGHTS INTO PATHOPHYSIOLOGY AND THERAPEUTIC IMPLICATIONS - Coradin, Julia; Castro, Yasmin Vitória Carvalho de; Caiado, Fernanda Leal; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Autism Spectrum Disorder (ASD) is a heterogeneous neurodevelopmental condition with a significant genetic component. Recent advances in genomic technologies have revolutionized our understanding of the genetic architecture of ASD, revealing a complex interplay of common and rare variants, de novo mutations, and epigenetic factors. This narrative review synthesizes current knowledge on the genetic underpinnings of ASD, highlighting key biological pathways, brain regions, and cell types implicated in its pathophysiology. We discuss the challenges and opportunities for translating genetic findings into clinical practice and explore emerging therapeutic strategies targeting the underlying molecular mechanisms of ASD. By integrating insights from genetics, neurobiology, and translational research, we provide a comprehensive overview of the current state of knowledge and future directions in ASD research.